Receptors for immunoglobulin G (FcyR) - Marzocchi-Machado, Cleni M.; Lucisano-Valim, Yara M. (Medicina (Ribeirao Preto), 2005)
Receptors for immunoglobulin G (FcyR) provide an important link between the humoral and cellular branches of the immune response. These receptors can trigger a variety of biological responses such as phagocytosis, endocytosis, capture and clearance of immune complexes, antibody-dependent cell citotoxicity and release of inflammatory mediators. Human FcyR belong to the Ig superfamily and three classes of these receptors are distinguished specifying many receptor isoforms. These molecules differ in affinity and specificity for IgG isotypes, cell distribution patterns, intracellular signal delivery and molecular weights. Moreover, the genetic polymorphism introduces variations among individuals. The structural and functional diversity makes these receptors potential targets for immunotherapy. Activation and deactivation of effector cells via FcyR can be exploited to develop novel therapies for cancer, infectious diseases and autoimmune disorders. This review describes structural and functional details, clinical relevance and some therapeutic use of the FcyR molecules.